Facile synthesis of cobalt ferrite nanotubes using bacterial nanocellulose as template - Menchaca Nal, Sandra (Elsevier, 2016)
A facile method for the preparation of cobalt ferrite nanotubes by use of bacterial cellulose nanoribbons as a template is described. The proposed method relays on a simple coprecipitation operation, which is a technique extensively used for the synthesis of nanoparticles (either isolated or as aggregates) but not for the synthesis of nanotubes. The precursors employed in the synthesis are chlorides, and the procedure is carried out at low temperature (90 °C). By the method proposed a homogeneous distribution of cobalt ferrite nanotubes with an average diameter of 217 nm in the bacterial nanocellulose (BC) aerogel (3%) was obtained. The obtained nanotubes are formed by 26-102 nm cobalt ferrite clusters of cobalt ferrite nanoparticles with diameters in the 9-13 nm interval. The nanoparticles that form the nanotubes showed to have a certain crystalline disorder, which could be attributed in a greater extent to the small crystallite size, and, in a lesser extent, to microstrains existing in the crystalline lattice. The BC-templated-CoFe2O4 nanotubes exhibited magnetic behavior at room temperature. The magnetic properties showed to be influenced by a fraction of nanoparticles in superparamagnetic state.